Clinicopathologic Features and Outcome of COVID-19 Patients Attended at a Secondary Hospital in Bangladesh during the Pandemic (Delta Medical College Journal, 2024)
Background: Coronavirus Disease 2019 (COVID-19) is an acute respiratory diseasethat can present varieties of clinical and pathologic manifestation. Sometimes it presentwith severe manifestation which ultimately lead to respiratory failure and death.COVID-19 patients with other comorbidities may develop a life-threatening situation.Objective: To describe the clinicopathologic features and outcome of COVID-19patients admitted in Combined Military Hospital (CMH) Rangpur, Bangladesh.Materials and method: This cross-sectional study was conducted at CMH Rangpur,Bangladesh, from 1 May 2021 to 30 August 2021 among purposively selected 416 casesof COVID-19 positive patients. Data were collected from the medical records of thehospital admitted patients in a structured case report form. Results: Highest numbers ofthe respondents were in the age group of 31-50 years (49.03%) with male predominance(72.28%). About 89% were Muslim and 54.81% were educated up to higher secondarylevel. Fever (90.86%) was the common presenting symptoms followed by cough(73.55%), sore throat (30.28%). About 24.51%, 23.07%, 11.05% had hypertension,diabetes mellitus and respiratory comorbidities respectively. Lymphopenia (75.24%)and elevated C-Reactive Protein (54.08%) were observed in most of the cases. Only8.17% patients had critical illness that needed intensive care unit admission. Majority(91.82%) fully recovered from the illness while 1.92% expired. Conclusions: The mostcommonly reported symptom was fever (90.86%) among all the COVID-19 positivepatients. Majority (62.25%) of the patients belonged to mild cases. Overall mortalitywas 1.92%. In most cases the clinical presentation is that of a respiratory infection withsymptom severity ranging from a mild influenza like illness.Delta Med Col J. Jan 2021;9(1):3-8